Ecopolis: Merging Competition and Sustainability Education in a Resource Management Game - Santos, Daniel dos; Costa, Fernando; Parreiras, Marcus; Xexéo, Geraldo; Magalhães, Marcos (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
This article introduces Ecopolis, a resource management game that imparts knowledge about sustainability and ESG+P pillars through engaging gameplay mechanics. Players learn about these concepts via interactive decision-making tasks, using game components like cards, a game board, and tokens. The game is available in Print ’n’ Play and digital versions. Following playtest sessions with four players, enhancements were made, particularly to the resource management aspects. The game received positive feedback for its effectiveness in teaching sustainability concepts. Future versions aim to improve game balance and introduce new dynamics.